The marijuana user in US news media: an examination of visual stereotypes of race, culture, criminality and normification. (May 2020) - Mortensen, Tara Marie; Moscowitz, Leigh; Wan, Anan; Yang, Aimei
In the wake of growing legalization efforts, both medicinal and recreational marijuana use in the US is becoming more prevalent and societally acceptable. However, racial, criminal and cultural stereotypes linger in mediated visual portrayals. This study examines the extent to which mediated visual portrayals in mainstream news have been impacted by these recent legalization efforts. Employing a quantitative as well as a qualitative analysis of visual images used to represent marijuana use in mainstream news, this study draws upon the power of visual framing and the construction of social reality to examine how visual symbols and iconic signifiers are used to construct both stereotypical and 'mainstreamed' or 'normative' depictions of marijuana use. Analyzing 458 visuals across 10 different media outlets across the political spectrum, both before and after legalization of marijuana in Colorado, this study shows how news portrayals perpetuated stereotypes about marijuana users, particularly around criminality and pot-culture iconography. Relatively few depictions of marijuana users in the US are visuals of ordinary, 'normal' people or families. This study thus interrogates the relationship between representations of race, criminality and 'pothead' stereotypes associated with marijuana use, and how these visual representations differ amongst liberal and conservative news sites, finding that the political ideology of the news outlet largely influences the visual stereotyping of marijuana users. The study concludes by considering both the legal and cultural implications of how mainstream news visually represents marijuana use, considering how persistent decades-old representations were largely perpetuated rather than challenged in light of legalization efforts.